Адаптивные особенности пищеварительной системы насекомоядных и зерноядных птиц - Воронов, Н.П. (Вестник зоологии, 1973)
A comparative-morphological analysis of the digestive system was performed for insectivorous (A pus apus L., Riparia riparia L., Motacilla alba L., Sturmus vulgaris L.) and granivorous (Coccothraustes coccothraustes L., Pyrrhula pyrrhula L., Carduelis carduelis L., Acanthis flammea L., .A. cannabina L.) birds. Adaptations of the digestive system to a definite type of fodder were detected. So, in the insectivorous birds the small and large intestines are shortened, but the duodenum is longer and has an extremely developed sucking apparatus (long, branching out fibres), the liver and pancreas are well developed. In the granivorous birds the weak development of the gizzard is compensated by the presence of a strong bill of crushing and shelling type, the weak development of the liver and pancreas — by the developed proventriculus as well as by the elongation of the small and large intestines.